Electrochemical synthesis of ferritic stainless steels alloyed with 1 wt-%Ti, V and Nb in sulphuric acid solution - Demiroren, H.; Aksoy, M. (Taylor & Francis Ltd, 2009)
Corrosion behaviours of stainless steel alloys containing corrosion resistant elements were investigated. Ferritic stainless steel electrodes were synthesised by the application of a scan rate of 1 mV s(-1). Stainless steels were unalloyed and alloyed with approximate 1 wt-% Ti, V and Nb elements. The samples were obtained from casting and forging. The steels were exposed to different heat treatments. Heat treatment was not applied to the first group of samples. The second and the third group of samples were rapidly cooled after annealing at 1100 degrees C for 30 and 180 min respectively. The corrosion performances of ferritic stainless steels were investigated in 0.1 M H2SO4 solution, by use of electrochemical impedance spectroscopy. Scanning electron microscopy (SEM) investigations were performed. Scanning electron microscopy micrographs showed generalised pitting on the surface. Corrosion resistance was calculated by Stearn-Geary equation. It was determined that titanium has the best effect on the corrosion resistance of ferritic stainless steels homogenised for 180 min.
Keywords: Ferritic stainless steel (FSS); Alloying element; Nyquist diagram; Sulphuric acid; Electrochemical impedance spectroscopy